Sistematização dos critérios estaduais de distribuição da cota-parte do ICMS: um olhar técnico e de governança - Mottin, Fátima (2022)
Among the main governmental transfers, the share of the ICMS, a state tax that significantly contributes to municipal revenues, stands out. This tax is transferred to the municipalities in a fractioned manner, as determined by Article 158 of the Federal Constitution, with the first part being proportional to what the municipality generates as tax to the state, and the second defined by criteria such as having state law. And, in this second part, Brazilian states use several criteria, related to various areas of public management, to determine an ICMS distribution index. In this sense, the present study aims to systematize the criteria used by the 26 Brazilian states in the distribution of the ICMS share, identifying the areas that receive greater attention from the states and if technically there is a concern with the elaboration of these criteria. In addition, the fact that the states define criteria for the distribution of the ICMS share converges with the function of governance to direct and monitor management actions, só that they can deliver public value to society. Thus, it is also intended to understand whether the criteria used can, in addition to serving as a basis for redistributing the tax, direct and monitor areas that deliver public value to society. To reach these objectives, this work used a bibliographic and documental research analysis methodology, in which the former brought theoretical references for the definition of the areas and for the construction of the Criteria Qualification Form, and the latter, with a ThematicCategorial Content Analysis approach, allowed a quantitative analysis of the criteria for the distribution of the ICMS share. The assumptions of this work are two, being first that the criteria in their technical composition may contain qualifications that impact more on their technical rigor, which was confirmed with the Firth Logistic Regression analysis, which pointed out the technical qualifications of sensitivity and simplicity as significant, being the ones that impact most on the criteria not fully meet the Criteria Qualification Sheet; and the second assumption that in most areas there are criteria that can be considered as a governance tool was also confirmed, since the criteria showed themselves as management drivers for better performance and reduction of social and territorial inequalities.